PENGARUH STIMULASI PEMBERIAN TABLET HISAP VITAMIN C TERHADAP PENINGKATAN SEKRESI SALIVA PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISA DI RS UMUM SEMBIRING - Rostiodertina Girsang; Dewi Tiansa Barus (Jurnal Penelitian Keperawatan Medik, 2019)
Chronic kidney failure is a progressive and irreversible decline in kidney function, in which the body is unable to maintain fluid balance and electrolyte metabolism. In practice, patients must limit the liquid diet to prevent complications. To reduce patient complaints, the action that can be done is to stimulate the salivary glands with chemical stimulation using acidic vitamin C lozenges. The purpose of this study was to determine the stimulating effects of vitamin C lozenges to increase salivary secretion in patients with chronic renal failure undergoing hemodialysis therapy at Sembiring General Hospital. This study used a Pre-experimental design with a pretest-posttest design. The sample amounted to 48 respondents, using Purposive Sampling techniques. Based on analysis conducted found significant differences amount of secretion of saliva before and after found a significant increase in the secretion of saliva between pretest saliva and posttest conclusion, the stimulation of the provision of lozenges vitamin C has the effect of increasing salivary secretion in patients with chronic kidney failure undergoing hemodialysis therapy at Sembiring General Hospital.